Transseptal direct complete annuloplasty: early experience - Rogers, Jason H.; Bolling, Steven F. (Annals of Cardiothoracic Surgery, 2020)
Annuloplasty is a fundamental component of surgical mitral valve repair, and is employed in nearly 100% of repair operations for both primary and secondary mitral regurgitation (SMR). Developing transcatheter techniques to replicate surgical annuloplasty has been the focus of significant innovation and development in recent years. Since many patients are not offered surgery due to high perceived surgical risk, transcatheter approaches will provide new treatment options. In this manuscript, we review technologies which allow transseptal and transcatheter mitral valve (MV) annuloplasty.